THE SOIL MOISTURE RETENTION PATTERN OF SOME SELECTED OF ORGANIC MEDIA UNDER A GREENHOUSE STRUCTURE - Dare, A.; Onwuegbunam, N. E.; Maikano, S.; Zakka, E. J. (FUDMA JOURNAL OF SCIENCES, 2020)
This research aimed to investigate the soil moisture retention of some selected organic media for growing cucumber plant. The experiment was conducted in a greenhouse structure and moisture content of each of the organic media was determined by a calibrated moisture meter, which was taken before and after the irrigation. The water application was uniform, using a drip irrigation kit for potted system with a capacity of 75cl storage each for the treatments. The pH values of each of the organic media used shows moderate alkalinity. The mean and sample variance of the moisture retention pattern for each of the media gave; saw dust (3.61, 0.073), maize husk (3.41, 0.044), rice husk (3.92, 0.034), eucalyptus leaves (3.27, 0.021), sawdust + soil (2.76, 0.0416), maize husk + soil (2.94, 0.153), rice husk + soil (3.88, 0.069), eucalyptus leaves + soil (2.76, 0.041), eucalyptus leaves + soil unsterilized (3.77, 0.074), and sandy loamy (23.345, 0.009). Moisture retention pattern of the selected media show high moisture retention in sandy loam while other media show a low moisture retention in approximately ratio 6:1, the sample variance shows small variance indicating how the data point spread out. It can be assumed that low retention could be as a result of the presence of fibre or coarse particles given room for large pore spaces that allows easy moisture drain from the organic media. It can also be deduced from the results that maize husk is least suitable for growing purposes because of unsteady moisture retention pattern.